Instructional Dynamics of Muḥādaṡah: Evaluating Pedagogical Methods and Institutional Barriers in an Indonesian Pesantren - J. Sutarjo (Fakultas Tarbiyah dan Keguruan, 2025)
Purpose – This study investigates the implementation of muḥādaṡah (Arabic conversation) instruction at Al-Muhsin Islamic Secondary School, Metro, Indonesia. Design/methods/approach – Using a descriptive qualitative approach, data were collected through participant observation, semi-structured interviews, and documentation. The study aims to evaluate the effectiveness of the curriculum, instructional methods, and the role of teaching staff. Findings – The results indicate that while the school adopts a modern pesantren curriculum, the pedagogical implementation remains traditional, relying heavily on the